Ustrój prawny samorządu rolniczego w Polsce i RFN. Studium porównawcze - Balcerek, Marta (Wydawnictwo Naukowe WNPiD UAM, 2012)
Two models of farmers’ institutions have developed in Europe: a) the French model, resulting from the decentralization of public administration and taking the form of agricultural chambers, or corporations under public law, administratively imposing obligatory membership, and b) the Anglo-Saxon model of voluntary agricultural associations with no administrative power. The purpose of this paper is to compare the first model, using the example of the North Rhine-Westphalia Chamber of Agriculture and the Wielkopolska Chamber of Agriculture. The differences are presented in terms of their respective legal structures and the tasks each chamber performs in the state administration of FRG and Poland.
The legal structure of agricultural self-governing bodies in Poland and the Federal Republic of Germany. A comparative study
Keywords: samorząd rolniczy; ustrój prawny; RFN; Polska